PENGARUH METODE PARTISIPATIF DAN KONSEP DIRI TERHADAP HASIL BELAJAR IPS PADA PROGRAM PAKET B - Budi, Rossa Candra; -, Sjarkawi -; Rusdi, Muhammad - (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2011)
Purpose of this study is to examine effect of participatory method and students’ self concept on the students’ achievement in the Social Studies subject of the Paket B program. The study used experimental 2x2 factorial design and was applied to four goups of Paket B in SKB Muaro Jambi with totally 80 students as samples.  As independent variables are participatory method and conventional method which are applied separately in experiment group and control group. The students’ self-concept is a moderator variable and students’ achievement is the dependent variable. A pre-test and post-test were administered, and the results were analyzed by two-way ANOVA and Tukey Test. The results revealed that (1) there was significant difference of students’ achievement between experiment and control groups; and (2) no effect of self concept on students’achievement as indicated by none significant difference of the upper and lower groups. For the upper and lower group, it can be concluded that (1) there was a significant difference of students’ achievement between experiment and control groups; and (2) there is no interaction between  methods of learning and students’ self concept in effecting students’ achievement. Keywords: participation method of learning, students’ self concept, students’ cognitive achievement